RELIGIOUS CHARACTER DEVELOPMENT: Madrasah Heads' Strategies in Educating Students in Bandung - Arifin, Nur; Kayadibi, Saim; Tabroni, Imam (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: The degradation of character among students has become a critical issue in many educational settings, especially within Islamic schools, where moral and spiritual development is paramount. Character education, particularly in religious contexts, plays a crucial role in shaping students into responsible and ethical individuals. Purpose: This study examines the strategies employed by Madrasah heads in Bandung to develop the religious character of their students, addressing the challenges posed by the ongoing degradation of character among youth. The cultivation of religious character is central to creating morally responsible and spiritually grounded individuals. This research aims to explore the policy formulation, implementation strategies, and evaluation processes employed by Madrasah leaders to foster religious character development. Method: Using a qualitative case study approach, data were collected through in-depth interviews, participant observation, and documentation. The data analysis followed an interactive model consisting of data collection, reduction, presentation, and conclusion. Result: The findings reveal that religious character formation is supported by habituation programs, such as Madrasah literacy, extracurricular activities, Qur’an recitation, prayer routines, and the 5S method (Smile, Greetings, Politeness, Cleanliness, and Orderliness). These activities, alongside regular evaluations, contribute to creating a disciplined and respectful environment. Conclusion: The research highlights the importance of leadership commitment and collaborative efforts in effectively implementing character education, suggesting that a strategic approach to character development can lead to positive changes in student behavior and spiritual growth.